Cybersecurity in Hospitals: An Evaluation Model - Mohammed A. Ahmed; Hatem F. Sindi; Majid Nour (Journal of Cybersecurity and Privacy, 2022)
Hospitals have been historically known for their strong risk mitigation policies and designs, which are not becoming easier or simpler to plan and operate. Currently, new technologies and devices are developed every day in the medical industry. These devices, systems, and personnel are in an ever-higher state of connection to the network and servers, which necessitates the use of stringent cybersecurity policies. Therefore, this work aims to comprehensively identify, quantify, and model the cybersecurity status quo in healthcare facilities. The developed model is going to allow healthcare organizations to understand the imminent operational risks and to identify which measures to improve or add to their system in order to mitigate those risks. Thus, in this work we will develop a novel assessment tool to provide hospitals with a proper reflection of their status quo, which will assist hospital designers in adding the suggested cyber risk mitigation measures to the design itself before operation.